Investation and Compare blood Pressure measurements taken by both components of stethoseope, bell and diaphragm - afazel M (Iran University of Medical Sciences, 1998)
This is a 9uasi experimental study to compare blood pressure measurements taken by both components of stethoscope, bell and diaphragm. Blood pressure was evaluated in fifty patients of fifteen years of age and older. Equal populations of both genders were selected randomly from infectious, surgery and internal medicine wards. Subjects with cardiac arrhythmia weren't included in the study. Five minutes before collecting the data subjects were in the supine position. Blood pressure was measured simultaneously by using a bell and a diaphragm on both arms by two trained examiners. The cuff on each arm was connected separately to two mercury sphygmomanometers and by a Y -connection to a single bulb. In order to leave out the effect of the difference in pressure in the two arms, blood pressure was measured with identical components of stethoscope at the same time, and the resulting difference was taken in to account in the computations. After computing the difference, resulting from the use of different tools bell or diaphragm) for blood pressure measurments, results showed that values measured by bell versus diaphragm in each of the three cases (systolic, first diastolic and second diastolic) were understimated (the mean difference being 0.56, 0.48 and 0.72 mmHg respectively). Statistical analysis of the result by the use of paired t-test indicated that there was no significant difference among those three cases. As a result, the three research hypotheses that predicated the existance of difference between systolic, first diastolic and second diastolic recordings measured by two different techniques, the bell and the diaphrgm, were rejected (P<0.05).